Tourism Development Of Gamelan As Tourism Attraction Unique Product Of Banyu Mudal Tourism Village - Dyah Palupiningtyas; Andhi Supriyadi; Trenggono Trenggono (UNUSA Press, 2021)
In today, to develop tourism potential in the area and also to increase income, village with the label of Tourism Village have emerged. Tourism Village is a self–help and self-subsistent, the community which in their social activities try to increase their own understanding of tourism, contributing to increasing value of tourism development within its territory, contributing to increasing value of tourism and its empowerment of welfare, participating to contribute the success of development of tourism. In this case, a tourism product is needed that the characteristics of the village so that it can distinguish it from other villages. Banyu Mudal Tourism Village is a Tourism Village that included in the Moga District, Pemalang Regency, Central Java Province which has the potential as Tourism Village with its natural beauty appeal. There are supporting of facilities and infrastructure such as road and transportation as well as human and institutional resources. Beside the potential, there are also shortcoming and problems that exist in the village. By holding a Focus Group Discussion (FGD) it was found that currently the village of Banyu Mudal does not have unique tourism product. In the tourist village of Banyu Mudal, there is a gamelan craftsman who has a studio to practice beating gamelan. This potential is promoted to be a superior product of gamelan music education tourism. Although there are some side which thing need to be addressed, such as facilities and infrastructure as well as marketing and quality of resources and require assistance.